Software and database for the analysis of mutations in the VHL gene. - Béroud, C (1998)
VHL is a tumor suppressor gene localized on chromosome 3p25-26. Mutations of the VHL gene were described at first in the heritable von Hippel-Lindau disease and in the sporadic Renal Cell Carcinoma (RCC). More recently, VHL has also been shown to harbor mutations in mesothelioma and small cell lung carcinoma. To date more than 500 mutations have been identified. These mutations are mainly private with only one hot spot at codon 167 associated with pheochromocytoma. The germline mutations are essentially missense while somatic mutations include deletions, insertions and nonsense. To standardize the collection of these informations, facilitate the mutational analysis of the VHL gene and promote the genotype-phenotype analysis, a software package along with a computerized database have been created. The current database and the analysis software are accessible via the internet and world wide web interface at the URL:http://www.umd.necker.fr